Student[Calculus1]
ImplicitDiffSolution
generate steps for implicit differentiation
Calling Sequence
Parameters
Description
Examples
Compatibility
ImplicitDiffSolution( f, y, x, opts )
f
-
algebraic equation
y
names or function of dependent variable
x
name of dependent variable
opts
(optional) options of the form keyword=value, where keyword is one of output, displaystyle, or animated
The ImplicitDiffSolution command computes the partial derivative of the function, y with respect to x, showing the steps required to make the computation. The input f defines y as a function of x implicitly. It must be an equation in x and y or an algebraic expression, which is understood to be equated to zero.
All other names, which appear in the input f and the derivative variable(s) x and are not of type constant, are treated as independent variables.
Optional arguments output, displaystyle, and animated can be passed to control the style of output. These options are described in Student:-Basics:-OutputStepsRecord. The return value is controlled by the output option.
This function is part of the Student:-Calculus1 package.
with⁡Student:-Calculus1:
ImplicitDiffSolution⁡x2+y3=1,y,x
Implicit Differentiation Stepsy3+x2=1•Rewriteyas a functiony⁡x:y⁡x3+x2=1•Differentiate the left sideⅆⅆxy⁡x3+x2▫1. Apply thesumrule◦Recall the definition of thesumruleⅆⅆxf⁡x+g⁡x=ⅆⅆxf⁡x+ⅆⅆxg⁡xf⁡x=y⁡x3g⁡x=x2This gives:ⅆⅆxy⁡x3+ⅆⅆxx2▫2. Apply thepowerrule to the termⅆⅆxx2◦Recall the definition of thepowerrule∂∂xxn=n⁢xn−1◦This means:ⅆⅆxx2=2⋅x1◦So,ⅆⅆxx2=2⋅xWe can rewrite the derivative as:ⅆⅆxy⁡x3+2⁢x▫3. Apply thechainrule to the termy⁡x3◦Recall the definition of thechainruleⅆⅆxf⁡g⁡x=f'⁡g⁡x⁢ⅆⅆxg⁡x◦Outside functionf⁡v=v3◦Inside functiong⁡x=y⁡x◦Derivative of outside functionⅆⅆvf⁡v=3⁢v2◦Apply compositionf'⁡g⁡x=3⁢y⁡x2◦Derivative of inside functionⅆⅆxg⁡x=ⅆⅆxy⁡x◦Put it all togetherⅆⅆxf⁡g⁡x⁢ⅆⅆxg⁡x=3⁢y⁡x2⋅ⅆⅆxy⁡xThis gives:3⁢y⁡x2⁢ⅆⅆxy⁡x+2⁢x•The final result is3⋅y⁡x2⋅ⅆⅆxy⁡x+2⁢x•Differentiate the right sideⅆⅆx1▫4. Apply theconstantrule to the termⅆⅆx1◦Recall the definition of theconstantruleⅆCⅆx=0◦This means:ⅆⅆx1=0We can now rewrite the derivative as:0•Rewriteⅆⅆxy⁡xasy'and solve fory'3⋅y2⋅y'+2⁢x=0•Subtract2⋅xfrom both sides3⋅y2⋅y'+2⋅x−2⋅x=0−2⋅x•Simplify3⋅y2⋅y'=−2⋅x•Divide both sides by3⋅y2y'⋅3⋅y23⋅y2=−2⋅x3⋅y2•Simplifyy'=−2⁢x3⋅y2•Solutiony'=−2⁢x3⁢y2
ImplicitDiffSolution⁡a⁢x3⁢y−2⁢yz=z2,y⁡x,z,x
Implicit Differentiation Stepsa⁢x3⁢y−2⁢yz=z2•Rewriteyas a functiony⁡x,z:a⁢x3⁢y⁡x,z−2⁢y⁡x,zz=z2•Differentiate the left side∂∂xa⁢x3⁢y⁡x,z−2⁢y⁡x,zz▫1. Apply thesumrule◦Recall the definition of thesumruleⅆⅆxf⁡x+g⁡x=ⅆⅆxf⁡x+ⅆⅆxg⁡xf⁡x=a⁢x3⁢y⁡x,zg⁡x=−2⁢y⁡x,zzThis gives:∂∂xa⁢x3⁢y⁡x,z+∂∂x−2⁢y⁡x,zz▫2. Apply theconstant multiplerule to the term∂∂xa⁢x3⁢y⁡x,z◦Recall the definition of theconstant multiplerule∂∂xC⁢f⁡x=C⁢ⅆⅆxf⁡x◦This means:∂∂xa⁢x3⁢y⁡x,z=a⋅∂∂xx3⁢y⁡x,zWe can rewrite the derivative as:a⁢∂∂xx3⁢y⁡x,z+∂∂x−2⁢y⁡x,zz▫3. Apply theproductrule◦Recall the definition of theproductruleⅆⅆxf⁡x⁢g⁡x=ⅆⅆxf⁡x⁢g⁡x+f⁡x⁢ⅆⅆxg⁡xf⁡x=x3g⁡x=y⁡x,zThis gives:a⁢ⅆⅆxx3⁢y⁡x,z+x3⁢∂∂xy⁡x,z+∂∂x−2⁢y⁡x,zz▫4. Apply thepowerrule to the termⅆⅆxx3◦Recall the definition of thepowerrule∂∂xxn=n⁢xn−1◦This means:ⅆⅆxx3=3⋅x2We can rewrite the derivative as:a⋅3⋅x2⋅y⁡x,z+x3⁢∂∂xy⁡x,z+∂∂x−2⁢y⁡x,zz▫5. Apply theconstant multiplerule to the term∂∂x−2⁢y⁡x,zz◦Recall the definition of theconstant multiplerule∂∂xC⁢f⁡x=C⁢ⅆⅆxf⁡x◦This means:∂∂x−2⁢y⁡x,zz=−2z⋅∂∂xy⁡x,zWe can rewrite the derivative as:a⁢3⁢x2⁢y⁡x,z+x3⁢∂∂xy⁡x,z+−2⁢∂∂xy⁡x,zz•The final result isa⁢3⁢x2⁢y⁡x,z+x3⁢∂∂xy⁡x,z−2⋅1z⋅∂∂xy⁡x,z•Differentiate the right side∂∂xz2▫6. Apply theconstantrule to the term∂∂xz2◦Recall the definition of theconstantruleⅆCⅆx=0◦This means:∂∂xz2=0We can now rewrite the derivative as:0•Rewrite∂∂xy⁡x,zasy'and solve fory'a⁢x3⁢y'+3⁢x2⁢y−2⋅1z⋅y'=0•Multiply through:a⋅x3⁢y'+3⁢x2⁢y=a⁢x3⁢y'+3⁢a⁢x2⁢ya⁢x3⁢y'+3⁢a⁢x2⁢y+−2⋅y'z=0•Subtract3⁢a⁢x2⁢yfrom both sidesa⁢x3⁢y'+3⁢a⁢x2⁢y+−2⋅y'z−3⁢a⁢x2⁢y=0−3⁢a⁢x2⁢y•Simplifya⁢x3⁢y'+−2⋅y'z=−3⁢a⁢x2⁢y•Find common denominatorz⋅a⁢x3⁢y'z+−2⋅y'z=−3⁢a⁢x2⁢y•Sum over common denominatorz⋅a⁢x3⁢y'−2⋅y'z=−3⁢a⁢x2⁢y•Multiply rhs by denominator of lhsz⋅a⁢x3⁢y'−2⋅y'z⋅z=z⋅−3⁢a⁢x2⁢y•Simplifyz⋅a⁢x3⁢y'−2⋅y'=−3⁢a⁢x2⁢y⁢z•Factory'⋅a⁢x3⁢z−2=−3⁢a⁢x2⁢y⁢z•Divide both sides bya⁢x3⁢z−2y'⋅a⁢x3⁢z−2a⁢x3⁢z−2=−3⁢a⁢x2⁢y⁢za⁢x3⁢z−2•Simplifyy'=−3⁢a⁢x2⁢y⁢za⁢x3⁢z−2•Solutiony'=−3⁢a⁢x2⁢y⁢za⁢x3⁢z−2
Output can be shortened by declaring some rules to be understood
Understand⁡diff,constant,power,constantmultiple
Diff=constant,power,constantmultiple
ImplicitDiffSolution⁡y3+x2=1,y,x
Implicit Differentiation Stepsy3+x2=1•Rewriteyas a functiony⁡x:y⁡x3+x2=1•Differentiate the left sideⅆⅆxy⁡x3+x2▫1. Apply thesumrule◦Recall the definition of thesumruleⅆⅆxf⁡x+g⁡x=ⅆⅆxf⁡x+ⅆⅆxg⁡xf⁡x=y⁡x3g⁡x=x2This gives:ⅆⅆxy⁡x3+ⅆⅆxx2•2. Apply thepowerrule to the termⅆⅆxx2ⅆⅆxy⁡x3+2⁢x▫3. Apply thechainrule to the termy⁡x3◦Recall the definition of thechainruleⅆⅆxf⁡g⁡x=f'⁡g⁡x⁢ⅆⅆxg⁡x◦Outside functionf⁡v=v3◦Inside functiong⁡x=y⁡x◦Derivative of outside functionⅆⅆvf⁡v=3⁢v2◦Apply compositionf'⁡g⁡x=3⁢y⁡x2◦Derivative of inside functionⅆⅆxg⁡x=ⅆⅆxy⁡x◦Put it all togetherⅆⅆxf⁡g⁡x⁢ⅆⅆxg⁡x=3⁢y⁡x2⋅ⅆⅆxy⁡xThis gives:3⁢y⁡x2⁢ⅆⅆxy⁡x+2⁢x•The final result is3⋅y⁡x2⋅ⅆⅆxy⁡x+2⁢x•Differentiate the right sideⅆⅆx1•4. Apply theconstantrule to the termⅆⅆx10•Rewriteⅆⅆxy⁡xasy'and solve fory'3⋅y2⋅y'+2⁢x=0•Subtract2⋅xfrom both sides3⋅y2⋅y'+2⋅x−2⋅x=0−2⋅x•Simplify3⋅y2⋅y'=−2⋅x•Divide both sides by3⋅y2y'⋅3⋅y23⋅y2=−2⋅x3⋅y2•Simplifyy'=−2⁢x3⋅y2•Solutiony'=−2⁢x3⁢y2
The Student:-Calculus1:-ImplicitDiffSolution command was introduced in Maple 2023.
For more information on Maple 2023 changes, see Updates in Maple 2023.
See Also
implicitdiff
Student:-Basics
Student:-Basics:-SolveSteps
Student:-Calculus1
Student:-Calculus1:-ShowSolution
Download Help Document